How does gift with purchase influence your satisfaction in online buying? - Ami Luki Andrian; Rokhima Rostiani (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Purpose – This study tries to examine the effectiveness of gift with purchase when utilized in a social media platform, measured through several variables: perceived usefulness, perceived quality, perceived ingenuity, and perceived cost. We believe that gift with purchase evoke a sense of surprise that leads individual to feel happier thus connects the effectiveness with happiness that subsequently influence individual loyalty.Design/methodology/approach – An online survey was conducted on 207 users of social media platforms for at least six months and received free gift with purchase.Findings – Perceived usefulness and perceived quality significantly influence happiness towards gifts with purchases. Perceived usefulness and perceived quality served as two important predictors for happiness. When consumers perceived they receive more values and benefits and good quality of the gift, their happiness will be significantly higher. Further, this study showed that happiness is a significant predictor for purchase satisfaction. When consumers are happy with their purchase, they report a higher satisfaction level on their buying decision and a particular seller's social media choice.Research limitations/implications – Results of this study have limited generalization due to sample’s characteristics. Further, this study did not differentiate between type of products such as hedonic or utilitarian that might influence how gift with purchase is perceived.Practical implications – This study provides insight into sellers participating in online shopping through social media to improve promotion strategy. Managers needs to show the information regarding usefulness and quality of free gift with purchase to their customers, thus showcasing the serious effort to keep consumer happy and satisfied.Originality/value – The inclusion of happiness variable is scant in research that tries to investigate the effect of gift with purchase and satisfaction. Although rare, happiness is closely related to gift with purchase that are free of charge and thus provide fresh insight on how satisfaction is created.